The Use Collaborative Strategy Reading to Improve Reading Comprehension - Wahyuni, Sri (English Language Education Program, Faculty of Education and Teacher Training, Sulthan Thaha Saifuddin State Islamic University of Jambi, 2017)
The problem of the study â€œWas there any significant difference in reading comprehension between the students who were taught by using CSR and those who were not to the eleventh graders of SMAN 1 Lintang Kananâ€. The objective of the study was to find out whether there was significant difference in reading comprehension between the students who were taught by CSR and those who were not. The technique applied in this study was quasi experimental method. The population of this study was all of the eleventh graders of SMAN 1 Lintang Kanan. The total number of population was 208 students. The sample of this research was taken by using purposive sampling. The number of sample was 70 students, consist of two classes were XI Science 3 and XI Science 4. Each class consisted of 35 students. The technique used for analyzing the data both of classes used paired t-test and independent sample t-test. Based on independet sample t-test, result showed that the mean score of post-test in experimental group was 78.26, standard deviation was 6.06. Result of post-test in control group was 62.76, standard deviation was 9.82 and the t-obtained was 7.828 at the significance level 0.000 and df 66, the critical value of t-table was 1.996. So, t-obtained was higher than t-table (7.828 > 1.996). The result showed that the mean score for two classes were different significantly. It means that the Alternative Hypotheses (Ha) was accepted and Null Hypotheses (Ho) was rejected.